2020
DOI: 10.1186/s13033-020-00413-3
|View full text |Cite
|
Sign up to set email alerts
|

Detection and prevalence of depression among adult type 2 diabetes mellitus patients attending non-communicable diseases clinics in Lilongwe, Malawi

Abstract: Background Depression is associated with chronic physical illnesses and negatively affects health outcomes. However, it often goes undiagnosed and untreated. We investigated the prevalence of depression among adult type 2 diabetes mellitus (T2DM) patients attending non-communicable diseases (NCD) clinics in Lilongwe, Malawi, and estimated the level of routine detection by NCD clinicians. This study set out to determine the prevalence of major depression and its detection among adult type 2 diab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 58 publications
(59 reference statements)
2
9
4
Order By: Relevance
“…At the same time, the prevalence of depression in this study was relatively lower than the prevalence rates of depression among patients with T2DM in Ethiopia (44.7%) [ 31 ] and in Rwanda (83.8%) [ 21 ]. However, the prevalence in our study was considerably higher than the prevalence rates of depression among patients with T2DM in Ghana (31.3%) [ 19 ] and Malawi (18%) [ 32 ]. The different prevalence rates obtained in these studies may be explained by the different methods used, including differences in the sample size, screening tools used for depression, different cut-off scores employed and sociodemographic statuses among the participants.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…At the same time, the prevalence of depression in this study was relatively lower than the prevalence rates of depression among patients with T2DM in Ethiopia (44.7%) [ 31 ] and in Rwanda (83.8%) [ 21 ]. However, the prevalence in our study was considerably higher than the prevalence rates of depression among patients with T2DM in Ghana (31.3%) [ 19 ] and Malawi (18%) [ 32 ]. The different prevalence rates obtained in these studies may be explained by the different methods used, including differences in the sample size, screening tools used for depression, different cut-off scores employed and sociodemographic statuses among the participants.…”
Section: Discussioncontrasting
confidence: 71%
“…Our study showed no significant association between gender and depression among patients with T2DM. A similar lack of association was observed among patients with T2DM in northern [ 23 ] and central Sudan [ 22 ], as well as in Malawi [ 32 ]. In contrast, gender was reported as a significant risk for depression among patients with T2DM in South Africa [ 40 ], Guinea [ 39 ], Ghana [ 19 ] and Rwanda [ 21 ].…”
Section: Discussionsupporting
confidence: 65%
“…We also observed that prevalence of depression in this study was lower than previous national estimate which was between 19% and 30% among adult primary healthcare attendees in Malawi [ 22 , 23 ]. This could be due to underdiagnosis due to inadequate diagnostic knowledge among health workers as a result of poorly integrated mental health care in cancer clinics Malawi [ 24 ].…”
Section: Discussioncontrasting
confidence: 58%
“…On the other hand, it might be that depression was underdiagnosed in our primary care population. A Spanish multicentre primary care study observed that 12 % of T2D patients had undiagnosed depression [ 37 ], and other studies from different clinics (not only primary care) have yielded similar percentages (17 and 18 %) [ 38 , 39 ]. Due to the increased mortality and cardiac event risks related to comorbid depression [ 40 ], and on the other hand, the favourable treatment outcomes of depression from glycaemic control [ 41 ], screening and treating depression among patients with T2D should definitely be a crucial part of T2D treatment.…”
Section: Discussionmentioning
confidence: 99%